A PRECISE STUDY ON “BERBERIS ARISTATA - NEMA, PRAKHAR; CHOURASIYA, AMBIKA; SHUKLA, AMIT; VISHWAKARMA, HARSHNA; JAIN, HARSHITA; JAIN, PRATEEK KUMAR (International Journal of Current Pharmaceutical Research, 2022)
Indian barberry is a very common plant with miraculous therapeutic activity. This plant was being used from very ancient times. It generally has Habitat of North-western Himalayas, Nilgiris, Kulu, and Kumaon. Propagation of this herb is carried out during the spring season. It is listed in “Ayurveda” for the treatment of various dysenteries. It is well known as “Daruhaldi” in Ayurveda because it is having properties like turmeric. It is also used in different systems of medication like in Ayurveda, Siddha, and Yunani. Twigs are either white or pale yellowish-brown in colour. The bark is having a pale brown appearance on the outside and has deep yellowish colour inside. Leaves are obovate, with reticulated venation, and are arranged in tufts of five to eight. These leaves are having a glossy dark green appearance on the outside and a light green colour inside. Flowers are yellow and are usually bisexual. The fruits are bright red. The stem is subterete, pale brownish yellow. It chiefly contains “berberine” as an active phytoconstituent that belongs to alkaloids. Other than berberine it also contains contain barbamine, oxyberberine, palmatine, and taxilamine. Roots of Berberis aristata contain berberine, barbamine, Jatrorrhizine, columbamine and oxyberberine. This plant is having various therapeutic activities like; antibacterial, antiperiodic, antidiarrheal, antipyretic, antidiabetic, and anticancer activities. Several research works were performed for this plant with the use of systemic animal models. A significant result was obtained. Investigations suggested that it can be used as an antimalarial, antioxidant, anti-inflammatory, hypoglycaemic, and hepatoprotective.